BIOFUMIGACIÃ“N Y SOLARIZACIÃ“N DEL SUELO EN LA PRODUCCIÃ“N DE SANDÃA (Citrulluslanatus (Thunb.) Matsum. &Nakai) - López-ElÃas, Jesús; Guerrero-RuÃz, José Cosme; Huez-López, Marco Antonio; Jiménez-León, José; Ruiz-Mendoza, José Jesús (European Scientific Journal, ESJ, 2014)
The implementation of techniques such as soil biofumigation and solarization, are an alternative to control diseases and weeds in the vegetable production. This study was carried out at the experimental field of the Sonora University, from July to December 2006. Soil solarization and biofumigation (incorporation of broccoli as organic matter) plus solarization effects on watermelon (Citrulluslanatus (Thunb.)Matsum.&Nakai) was evaluated. The transplant was carried out on August 15, 2006. The experimental design was a completely randomized with six replications. Yield and fruit quality of watermelon, Fusarium and nematodes presence,weeds presence, also mineral nutrition from soil and plant were evaluated. The combination of both techniques (soil biofumigation plus solarization) increased the total yield and fruit weight. Total solid soluble and fruit firmness were not affected by soil solarization and biofumigation plus solarization, not influencing the fruit quality. Soil solarization as well as its interaction with biofumigation significantly reduced the presence of Fusarium and nematode presence.The weed presence was efficiently controlled by soil solarization.The phosphorus and potassium fertilization can be reduced with soil biofumigation plus solarization. The total nitrogen and zincin plant was enhanced with soil solarization, while the manganeseabsorption was increased with the soil biofumigation and solarization combination.